Study influence of defects on the natural oscillation frequencies parts power plants - O. V. Vladimirov; A. R. Zagretdinov; I. V. Ivshyn; M. F. Nizamiev (Известия высших учебных заведений: Проблемы энергетики)
The results of studies of the influence of defects on the natural frequencies of the turbocharger turbine housing. The studies were conducted by means of finite element modeling software ANSYS and developed a program to generate images of vibro-acoustic research object in the graphical programming environment LabVIEW. Experimental studies on the turbocharger turbine housing using designed and developed measurement -diagnostic complex. Work performed under contract with the Ministry of Education of the Russian Federation from "12" February 2013 № 02.G25.31.0004.